Detection of HLA‐C*04:212, a novel HLA‐C*04 variant, in a Taiwanese hematopoietic stem cell donor. (22nd February 2016) - Yang, E. K. L.; Ng, J.; Lazaro, A.; Hung, J. H.; Lin, P. Y.
Abstract : Recombination and point mutation may result the formation of HLA‐C*04:212 .